“Dear caregiver, embrace the unique way”: Designing Virtual Reality (VR) for children with spectrum disorder / Muhamad Hafiz Hassan ... [et al.] - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Abdullah, Mohamad Hariri; Isa, Badrul (2022)
This chapter highlight the usability perception for overcoming the problem of sensory special needs to children with autism. Sensory processing disorder is a condition in which the brain has trouble receiving and responding to information that comes in through the senses. Formerly referred to as sensory integration dysfunction, it is not currently recognized a distinct medical diagnosis.Some children with sensory processing disorder are oversensitive to things in their environment of their life. Therefore, one educational tool should be developed in order to help children with autism by implementing and introducing interactive learning process. In this paper, researchers had focus on developing new tools to get focusing to children with autism by designing Virtual reality (VR) that special to them with putting the element and design criteria according to their need.